Analysis of factors and conditions forming the spatial-innovation-agri-entrepreneurial ecosystem of the depressed republics of the North Caucasus - V. Prokhorova, Viktoriya (Revista San Gregorio, 2019)
In the context of globalization, sanctions and increasing competition, new social, economic, technical, environmental and other “challenges” arose before society. All this, while organizing sustainable and balanced development of the national economy, requires intensifying the search for new tools of “answers”. Moreover, the complexity of new problems mobilizes the search for effective “answers” and forces them to not only anticipate these answers, but also to be adequate and sufficiently effective. Undoubtedly, the adequacy of the “answers” depends not only on timeliness, but also on their consistency and complexity. One of the priority areas of such a “response” to global and local challenges of our time should be the technological modernization of the sectors of the economy of the national economy, including assessment of the effectiveness and importance of agribusiness, taking into account the environmental component in the model of modernization of the national economy. We are convinced that consideration of purely economic and economic parameters alone is no longer sufficient — attention must also be paid to the social, environmental and cultural characteristics of Russia; in our case, to the regions of the North Caucasus. And this is natural, because in rural areas, in villages, the foundations of the universal human spirituality of any nation of the country are concentrated and placed. This confirms our message that the Russian national system of values must be included in the context of the architecture of the development of the national economy of the Russian Federation. It is well known that historically, agriculture has always been conservative and almost always forced to confront the diverse "challenges" of natural, weather, climate, social and other factors alone. Moreover, the agrarian sector never possessed sufficient financial resources, did not have adequate mechanisms, was provided with material resources according to the final principle, etc., which all ages put the strategically important sector of the national economy under consideration in unusual development conditions. At the same time. the rich experience of advanced agrarian developed countries suggests that agriculture initially has the properties in order to become one of the rather efficient sectors of the national economy. True, it should be noted - with proper state support and state regulation of agriculture in accordance with the laws of a market economy. This approach allows not only to eliminate the negative impact of natural, climatic, social and other factors and conditions, but also to expand economic and economic opportunities. The Russian realities of the development of agricultural enterprises are no longer able to satisfy the demands of theory and practice. All this actualized the topic of our study.